Investigation of Particle Gradation Effect on Soil-Rock Mixture Using Direct Shear Test - Salimun, Norsyafiqah; Mohamad, Hisham (International Journal of Integrated Engineering, 2024)
Soil-rock mixture (SRM) is a special geomaterial that is composed of soil and a certain percentage of rock blocks with various sizes and strengths. It has high structural strength and renewable resources that are used as filler in subgrade, construction material and embankment dams. However, the mechanical properties of the soil-rock mixture are sophisticated owing to the complicated interaction between soil and rock particles. Previously, many experimental investigations were conducted to focus on shear behaviours and the influencing factors of SRM. Yet, limited work has been done to underline the effect of particle size distribution towards SRM shear strength parameters. Thus, this study conducted an SRM shear test with three different kinds of gradation and rock block percentages. Various soil densities, porosities and different framework structures have resulted from different rock particle concentrations. From the results, the well-graded SRM shows a non-linear trend of cohesion value while uniformly graded and gap-graded SRMs shows contradicting trend respectively. The result and analysis in this study are especially useful in analysing its influence on the shear strength parameters of SRM with different rock block percentages.